2004
DOI: 10.1021/ie034312x
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidative and Catalytic Biomass Gasification in Supercritical Water:  A Promising Flow Reactor System

Abstract: We have developed a flow reactor system that smoothly gasifies glucose and glucose-lignin mixture solution at 673 K, 25.7 MPa. The reactor system consists of three continuous reactors, which are a pyrolysis reactor, an oxidation reactor, and a catalytic reactor. We have investigated the reactions that occurred in each reactor and evaluated favorable residence time. We have succeeded in achieving high gasification efficiency based on carbon up to 96% at 673 K, 25.7 MPa with total residence time of about 1 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 36 publications
0
47
1
Order By: Relevance
“…The different lignin monomer units (p-coumaryl, coniferyl, and sinapyl alcohols) as well as the multiplicity of bond types, illustrate its heterogeneity. [1][2][3] Three general routes for lignin conversion exist: 1) conversion to synthesis gas, [4][5] 2) production of bio oil through pyrolysis or liquefaction, [6][7] and 3) hydrolysis to produce monomer and/or oligomer units. [8][9] The first two routes demand severe conditions, whereas hydrolysis is comparatively mild.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The different lignin monomer units (p-coumaryl, coniferyl, and sinapyl alcohols) as well as the multiplicity of bond types, illustrate its heterogeneity. [1][2][3] Three general routes for lignin conversion exist: 1) conversion to synthesis gas, [4][5] 2) production of bio oil through pyrolysis or liquefaction, [6][7] and 3) hydrolysis to produce monomer and/or oligomer units. [8][9] The first two routes demand severe conditions, whereas hydrolysis is comparatively mild.…”
Section: Introductionmentioning
confidence: 99%
“…Boric acid is known to form esters B(OR) 3 with alcohols in neutral and borate esters NaB(OR) 4 in basic aqueous solutions, and thus it was expected that phenolic compounds would form the corresponding esters. In addition to blocking reactions of phenols, boric acid can also act as catalyst for the acidic ether hydrolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The gasification of lignin is needed for its efficient use as a high quality energy source for fuel cell or as liquid fuel by Fisher-Tropsch reaction. Supercritical water (T c = 647.3 K, P c = 22.1 MPa) gasification is a promising technique to reduce the lignin gasification temperature [2][3][4]. We have reported that lignin was converted to alkylphenol and formaldehyde via hydrolysis in supercritical water and then alkylphenol and formaldehyde decomposed to gaseous products over metal catalysts [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 ), and to chemicals include gasification [9], pyrolysis [10], ionic liquid catalysis [11], and hydrogenolysis over precious metal catalysts [12][13][14][15][16]. While these results are encouraging, the process requires costly hydrogen as a feed gas and, in some cases, suffers from low selectivity.…”
Section: Introductionmentioning
confidence: 99%